A General Overview of the Educational Programmes of the Hungarian Football Academies - Imre Fenyő; Dávid Rábai (Debrecen University Press, 2020)
In the course of our research, we surveyed the educational programmes of the football academies of Hungary. We wished to reveal the educational aspects of the life of the students at the football academies. The purpose of our project is to comparatively analyse the formal and conceptual dimensions of the educational programmes of the academies through an analysis of the documents of the academies concerned. We also conducted semi-structured interviews with the heads of the social- and educational sections of the academies (N=6). We used the results of the interviews to check-confirm or refute-the results we found. We believe that the findings of our research make it possible for us to better understand the elements and value-based components of the educational dimensions of the football academies. In this way, our survey is similar to the projects of researchers who worked with local educational programmes (for example, Brezsnyánszky et al., 2000). As a conclusion of our research, we may point out that both the formal and conceptual dimensions of the educational programmes of the individual football academies are strongly heterogeneous, and the quality of their pedagogical programmes is often questionable. The results yielded by the analysis of the interviews suggest that although an educational-social department is present at each of the academies, some our former conclusions in connection with the general standards of the educational work were confirmed by the answers we received from our respondents. The academies, almost without an exception, produce their own educational programmes and carry out their educational work individually, and do not cooperate with the other institutions. There is, consequently, no uniform and standard educational work, and there is no professional documentation of the work going on either. In this way, the quality of educational work is not really able to improve.